Impacts of Metarhizium brunneum F52 infection on the flight performance of Asian longhorned beetles, Anoplophora glabripennis - Clifton, Eric H. (PLoS One, 2019)
The Asian longhorned beetle (ALB), Anoplophora glabripennis, is an invasive wood-borer in North America and Europe that threatens a variety of tree genera, including Acer and Populus. All invasive ALB populations occur in quarantine zones where they are under eradication, a process that is difficult and expensive, requiring extensive surveys and host tree removals. Although ALB has been described as an insect that is typically slow to disperse, some rare individuals that fly longer distances have the potential to start infestations outside of quarantine zones. Biological control using entomopathogenic fungi has been considered as another option for managing ALB infestations. The entomopathogenic fungus Metarhizium brunneum strain F52, registered for commercial use in the United States, is effective at killing ALB adults but information is lacking on how this entomopathogen affects ALB flight behavior before death. Using quarantine-reared ALB, flight mills were used to collect data on flight performance of beetles at multiple time points after infection. Healthy (uninfected) male ALB adults always flew significantly greater distances than females. The maximum observation for total flight distance was a healthy male that flew 10.9 km in 24 hours on a flight mill. ALB adults infected with M. brunneum F52 flew significantly shorter distances compared to healthy adults, starting one week after fungal exposure. Biological control of ALB with this fungal entomopathogen could help to reduce their dispersal in the environment and, thereby, decrease the risk of adults moving outside of quarantine zones.